Influencing the state of public awareness of organ transplantation - Użdalewicz, Zofia; Mess, Eleonora (Nursing Problems / Problemy Pielęgniarstwa, 2016)
Introduction. Transplantation is considered to be one of the best, and in many cases the only treatment for end-stage organ failure. Unfortunately, the number of recipients awaiting donation is much greater than the number of donors, and this difference tends to increase. Long waiting times affect patients' health deterioration, and in some cases may even lead to death. For this reason, it is important to create a dynamically functioning system of coordinators who facilitate the acquisition of recipients. Purpose. The aim of the study was to investigate the factors influencing the state of public awareness of organ transplantation. Materials and methods. A survey conducted in January and February with the participation of 57 randomly selected representatives of medical professions and 57 randomly selected persons with non-medical education. The research was carried out in several major Polish cities: Kraków, Wrocław, Olsztyn and Szczecin. A research tool, deployed to carry out the research was an anonymous survey questionnaire of own authorship consisting mostly of multiple choice questions. Results and conclusions. There have been different levels of knowledge between the two groups. Health professionals gave more correct answers than respondents working in professions other than medical. The factors that affect the level of the respondents' knowledge include age, education and ethical-social aspects. With the increase in the level of knowledge and knowledge of transplantation issues there increases awareness and understanding in order to save another human being.